Fescue Hay Cost-Return Budget in Central and Eastern Kansas - O'Brien, Daniel; Shoup, Douglas; Duncan, Stewart R.; Dhuyvetter, Kevin C. (My University, 2014)
This publication provides estimated cost and returns for forward farm planning for fescue hay in central and eastern Kansas.
MF2146_2014_02
Keywords: MF2146; Crops; Economics; MF